Tinjauan Satu Dekade Kebijakan Nasional Pembangunan Desa Berkelanjutan di Indonesia - Hakim, Muhammad Lukman; Hanif, Nita Aribah (Journal of Social Contemplativa, 2025)
This study aims to examine the dynamics of sustainable village development policy in Indonesia over the past decade, particularly since the enactment of Law Number 6 of 2014 on Villages through to the 2020–2024 National Medium-Term Development Plan (RPJMN). Using a qualitative method with a literature review approach, this research analyzes national policy documents, regulations, and relevant academic and institutional publications. The findings reveal a paradigm shift in village development from a physical-infrastructure focus to a more holistic and sustainable approach, especially through the adoption of the Village SDGs framework. However, implementation at the village level faces significant challenges, including limited institutional capacity, weak monitoring and evaluation systems, and fragmented inter-ministerial regulations. Moreover, there remains a gap between policy planning and the actual socio-economic and environmental conditions of rural communities. This study recommends strengthening local capacities, improving policy harmonization across sectors, and developing evaluation systems based on sustainability indicators to ensure that the principles of sustainable development are realized at the village level.